PENGARUH CURRENT RATIO (CR),DEBT TO EQUITY RATIO (DER),DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PT. INDOFOOD SUKSES MAKMUR Tbk. - Sri Maylani Pratiwi; Miftahuddin Miftahuddin; Wan Rizca Amelia (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
AbstractThe food industry is a fairly large and rapidly growing group of companies in Indonesia. This industry is also one of the industries whose growth is quite good. The development of this industry is inseparable from the population of Indonesia which continues to grow each year. As the population grows, the volume of demand for consumption products also rises. The purpose of this study is to determine the effect of CR, DER, and EPS on Share Prices at PT. Indofood Sukses Makmur Tbk. This type of research is causal associative research which aims to analyze the relationship between one variable with another. The population in this study are all financial reports on PT.Indfood Sukses Makmur Tbk. The sample used is the financial statements at PT. Indofood Sukses Makmur Tbk from 2009-2018. The method of data analysis is done by multiple linear regression. The results showed that the CR, DER and EPS significantly influence stock prices